Menjadi Guru Multitalenta: Peran Penting sebagai Administrator Sekaligus Motivator di Kelas - Innas Mutiah; Mutiara Sari; Muzammil Khoiri; Annum Batubara (Indo Publishing, 2026)
The teaching profession requires broad competencies, not only as an instructor but also as an administrator and motivator in the learning process. This article aims to examine the important role of teachers as both administrators and motivators in the classroom, as well as how these two roles complement each other in creating effective, planned, and meaningful learning. This study employs a descriptive qualitative approach using a library research method, with data obtained through the exploration and analysis of relevant scientific journals, books, and previous research findings. The results show that the teacher's role as an administrator is reflected in the ability to prepare, manage, and document learning instruments such as annual programs, semester programs, syllabi, lesson plans, teaching journals, and grade records in an orderly and accountable manner. Meanwhile, the teacher's role as a motivator is reflected in the ability to foster students' learning enthusiasm through giving appreciation, creating an enjoyable learning atmosphere, and serving as an inspiring role model. These two roles form a continuous cycle of planning, implementation, evaluation, and motivation in learning, making the strengthening of teacher competencies in both aspects a fundamental necessity in efforts to improve the quality of learning, including in the context of Islamic Religious Education.